Factors Associated with Vertical and Horizontal Faith Maturity at a Christian University. Issue 1 (2nd January 2022) - Burtt, J. J.; Jones, Rory; Cox, Jonathan; Mize, Dahron; Dougherty, Kevin D.; Glanzer, Perry L.; Schnitker, Sarah A.
Abstract: Christian colleges strive to nurture the religious faith of students. Our study examines the relationship of curricular and co-curricular activities on two dimensions of faith maturity—vertical and horizontal. Analysis of survey data from seniors at one Christian university showed that the factors of discussing religion with peers and spending time with people of the same faith are associated with higher levels of vertical faith maturity, and discussing meaning/purpose with peers and volunteering are associated with higher levels of horizontal faith maturity. Participating in religious retreats, food or clothing drives, and workshops on racial/cultural awareness are related to both forms of faith maturity. We conclude with suggestions for implementation.